Influence of wheel-diameter difference of the same locomotive on ride quality of locomotive. (September 2020) - Zhao, Bin; Liu, Fei; Li, Ruiyu; Wang, Jianming; Liang, Lin; Luo, Ailing
Abstract: The existence of wheel-diameter difference of track locomotive will directly affect the motion performance of locomotive. In this paper, the creep force of coaxial wheel-diameter difference is analysed, and the dynamic model of 2-axle bogie locomotive is established by SIMPACK software. Based on the study of two typical wheel-diameter difference of the same bogie, 10 special working conditions of wheel-diameter differences of the same locomotive are put forward. The effects of different working conditions and different wheel-diameter differences of the same working condition on the straight line motion performance of locomotive are analysed. The results show that, the lateral displacement and lateral ride quality index of locomotive body increase with the increase of wheel-diameter difference under the same working condition, and they do not exceed the safety limit. The change of wheel-diameter difference has little effect on the vertical ride quality index of locomotive body. According to the lateral displacement of the locomotive body, the 10 working conditions are divided into three grades. The third grade (working condition 4, working condition 5, working condition 8 and working condition 11) is more conducive to the safe and stable motion of the locomotive. Therefore, in the wheel matching installation and repairing process, priority should be given to the arrangement of wheel-diameter difference of the same locomotive in the third grade. This will provide a reference and basis for the scheme of locomotive wheel economic repairing.